Frequency of Left Anterior Descending Artery Involvement as a Culprit Vessel in Young Patient with ST Elevation Myocardial Infarction - Mehwish Sabeen, Ghulam Kubra, Maroof Hassan, Faiza Sikandari, Deebaj Nadeem, Asma Murtaza (Pakistan Journal of Medical & Health Sciences, 2023)
Objective: To determine the frequency of left anterior descending artery involvement as a culprit vessel in young patient with ST elevation myocardial infarction (STEMI) at tertiary care hospital. Study Design: A cross-sectional study. Place and Duration: The Department of Cardiology, “National Institute of Cardiovascular Diseases, Karachi” Pakistan from October 2019 to April 2020. Methodology: Patients of both genders aged 25-45 years who were presented with onset of chest pain for more than 30 minutes with STEMI were included. All patients were clinically evaluated after detailed history. Routine biochemistry investigations were asked and ECG and echocardiography were performed. Frequency of left anterior descending artery involvement in patients with STEMI was noted. Results: In a total of 191 patients, mean age was 33.6±6.7 years while mean duration of chest pain was 42.5±8.3 minutes. There were 135 (70.7%) male and 56 (29.3%) female cases. In distribution of vessel disease, 76 (39.8%) had single vessel disease (SVD), 37 (19.37%) had double vessel disease (DVD) while 78 (40.84%) had triple vessel disease (TVD). Left anterior descending artery found to be positive in 88 (46.1%) patients. Practical Implications: To reduce the complications of STEMI, it is very important to increase the awareness and proper knowledge in the general public. Conclusion: Involvement of left anterior descending artery as a culprit vessel was fairly common in young patient with ST elevation myocardial infarction. Keywords: Left anterior descending artery, culprit vessel, ST elevation myocardial infarction, coronary artery disease.